Apnoea–hypopnoea index of 5 events·h−1 as a metabolomic threshold in patients with sleep complaints. Issue 1 (9th January 2023) - Kiens, Ott; Taalberg, Egon; Ivanova, Viktoria; Veeväli, Ketlin; Laurits, Triin; Tamm, Ragne; Ottas, Aigar; Kilk, Kalle; Soomets, Ursel; Altraja, Alan
Background: The apnoea–hypopnoea index (AHI) forms the basis for severity of obstructive sleep apnoea (OSA), a condition expected to reprogramme metabolic pathways in humans. We aimed to identify the AHI breakpoint from which the majority of significant changes in the systemic metabolome of patients with sleep complaints occur. Methods: In a prospective observational study on symptomatic individuals, who underwent polysomnography for the diagnosis of OSA, profiles of 187 metabolites including amino acids, biogenic amines, acylcarnitines, lysophosphatidylcholines, phosphatidylcholines and sphingomyelins were analysed with liquid chromatography mass spectrometry in peripheral blood drawn at three different time points overnight. Comparisons of rank-transformed data using a general linear model for repeated measures after dichotomising the study group at different AHI levels were applied to define the best cut-off based on Cohen's f. Results: 65 subjects were recruited with a median AHI of 15.6 events·h −1 . The mean Cohen's f over the metabolites was highest (0.161) at an AHI level of 5 events·h −1 representing the metabolomic threshold. Of the particular between-group differences, eight phosphatidylcholines, nine acylcarnitines and one amino acid (threonine) had significantly lower concentrations in the individuals with an AHI level equal to or above the metabolomic threshold. The metabolomic changes at AHI levels defining moderate and severe OSA were smaller than at an AHI of 5 events·h −1 . Conclusions: The metabolomic threshold for patients with sleep complaints described in this report for the first time coincides with the AHI threshold required to confirm the diagnosis of OSA. The metabolomic breakpoint coincides with the apnoea–hypopnoea index threshold of ≥5  events·h −1 required to confirm the diagnosis of obstructive sleep apnoea in patients with sleep complaints https://bit.ly/3SIswFC